Potential biomarkers to predict return to fertility after discontinuation of female contraceptives—looking to the future - Cordova-Gomez, Amanda; Wong, Andrew P.; Sims, Lee B.; Doncel, Gustavo F.; Dorflinger, Laneta J. (Frontiers in Reproductive Health, 2023)
Nowadays there are a dozen types of contraceptive methods, from reversible to permanent, for those choosing to delay pregnancy. Misconceptions about contraception and infertility are a key factor for discontinuation or the uptake of family planning methods. Regaining fertility (the ability to conceive) after contraceptive discontinuation is therefore pivotal. Technical studies to date have evaluated return to fertility by assessing pregnancy as an outcome, with variable results, or return to ovulation as a surrogate measure by assessing hormone levels (such as progesterone, LH, FSH) with or without transvaginal ultrasound. In general, relying on time to pregnancy as an indicator of return to fertility following contraceptive method discontinuation can be problematic due to variable factors independent of contraceptive effects on fertility, hormone clearance, and fertility recovery. Since the ability to conceive after contraceptive method discontinuation is a critical factor influencing product uptake, it is important to have robust biomarkers that easily and accurately predict the timing of fertility return following contraception and isolate that recovery from extrinsic and circumstantial factors. The main aim of this review is to summarize the current approaches, existing knowledge, and gaps in methods of evaluating return-to-fertility as well as to provide insights into the potential of new biomarkers to more accurately predict fertility restoration after contraceptive discontinuation. Biomarker candidates proposed in this document include those associated with folliculogenesis, cumulus cell expansion, follicular rupture and ovulation, and endometrial transport and receptivity which have been selected and scored on predefined criteria meant to evaluate their probable viability for advancement. The review also describes limitations, regulatory requirements, and a potential path to clinically testing these selected biomarkers. Predictive biomarkers, if easy and low-cost, have the potential to enable robust evaluation of RTF, and provide potential users the information they desire when selecting a contraceptive method. This could lead to expanded uptake and continuation of modern contraception and inform the development of new contraceptive methods to widen user’s family planning choices.